2023
DOI: 10.1039/d2an01850k
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in colorimetric sensors based on nanozymes with peroxidase-like activity

Abstract: Nanozymes have been widely used to construct colorimetric sensors due to their advantages of cost-effective, high stability, good biocompatibility, and ease of modification. The emergence of nanozymes greatly enhances the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 154 publications
(187 reference statements)
0
18
0
Order By: Relevance
“…Nevertheless, nanomaterial-based enzyme mimics, also known as nanozymes, have drawn more and more attention in the field of colorimetric sensors in recent times due to their superior stability, great catalytic activity, ease of preparation, and cost-effectiveness compared to natural enzymes. 9 In the past years, several nanomaterials that display incredible peroxidase-like activity have been reported. In 2007, researchers published the first evidence of the intrinsic peroxidase-mimicking activity of Fe 3 O 4 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, nanomaterial-based enzyme mimics, also known as nanozymes, have drawn more and more attention in the field of colorimetric sensors in recent times due to their superior stability, great catalytic activity, ease of preparation, and cost-effectiveness compared to natural enzymes. 9 In the past years, several nanomaterials that display incredible peroxidase-like activity have been reported. In 2007, researchers published the first evidence of the intrinsic peroxidase-mimicking activity of Fe 3 O 4 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic studies showed that Au HOPs-10 followed the ping-pong multisubstrate mechanism like HRP. Finally, POD mimics were applied to the colorimetric detection of disease-related biomarkers. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, colorimetric methods using nanomaterials with enzyme-mimic activities (nanozymes), as alternatives to the LSPR approach, have received intense attention in detection of various analytes. 15 Nanozymes mimic the function of natural enzymes with the added advantage of low cost, high stability, and surface tunability. [15][16][17] Nanozymes, like the natural enzymes, catalyze the conversion of substrates to oxidized colored products.…”
Section: Introductionmentioning
confidence: 99%
“…15 Nanozymes mimic the function of natural enzymes with the added advantage of low cost, high stability, and surface tunability. [15][16][17] Nanozymes, like the natural enzymes, catalyze the conversion of substrates to oxidized colored products. By keeping the concentration of the substrate constant, it is possible to develop a colorimetric method where the intensity of the colored products can be analyzed by the naked eyes or by absorption spectrophotometer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation